Effects of a maintenance period on ambulatory blood pressure and morning blood pressure surge in young normotensives post isometric training - Baross, A. W.; Baxter, B. A.; Wright, B. H.; Kay, A. D. (Frontiers in Physiology, 2024)
Isometric resistance training (IRT) has emerged as an efficacious therapeutic intervention to reduce ambulatory blood pressure (BP), and BP diurnal variability. However, once the required decreases in BP have been achieved the efficacy of implementing a reduced maintenance dose is not understood. Therefore, the purpose of this study was to determine the effects of an 8-week maintenance period (8-week) following the cessation of the prescribed 8-week IRT in young normotensives. Twenty-five two recreationally active, not resistance trained, normotensive (24-h ambulatory SBP, ≥130 mmHg) young adults were randomly assigned to a training-maintenance (TG-MT; n=13 [female=5]; age 21±2 years) or a nontraining control (CON; n=129 [female=4]; age 232±4 3 years) group. Ambulatory BP, morning BP surge (MBPS) and average real variability (ARV) were measured prior to, after 8 weeks of bilateral leg IRT (4x2-minute contractions at 20% MVC with 2-minute rest periods, 3 days/week) and following an 8-week (once per week) maintenance period. On completion of the maintenance period the significant reductions seen following the IRT were maintained within the TG-MT group in 24-h ambulatory SBP (6±4mmHg, P<0.001), daytime (5±5mmHg, P=0.002), MBPS (7±10mmHg, P=0.019) and 24-h SBP ARV (2.03±1.44mmHg, P=0.001), daytime SBP ARV (2.04±1.78mmHg, P=0.003). These results show that reductions in ambulatory BP (24-h SBP and daytime SBP), in addition to BP diurnal variations (MBPS, 24-h SBP ARV and daytime SBP AVR) are maintained following an 8week maintenance dose in young adults and add further weight to the growing body of evidence promoting IRT as an efficacious therapeutic exercise intervention to prevent or reduce BP.